Characteristics of Patients Attending an Ophthalmic Outpatient Department at the Cerebral Palsy Association of Coimbra - Pinheiro, Rosa Lomelino (2021)
Introduction: To assess visual impairment diagnosis, management, and consequences in patients with cerebral palsy at the Cerebral Palsy Association of Coimbra. Methods:  This is a cross-sectional, descriptive study. A retrospective review of consecutive medical records was performed on 102 patients diagnosed with CP attending ophthalmology appointments between 2018 and 2019. The components of a detailed ophthalmologic evaluation, diagnostic tools, and methods to increase cooperation were recorded. We characterized cerebral palsy according to its etiology, type and resulting motor impairment. Visual function assessment included visual acuity, contrast sensitivity, stereopsis, and visual field. Ocular motility and anterior eye assessment with slit-lamp biomicroscopy results were also recorded. Performance on visual tasks such as eye hand coordination, visual spatial perception, and fix and follow were evaluated. Results: The study included 102 patients aged from 10 months to 40 years. Regarding motor dysfunction classification, tetraplegia was the most prevalent type, followed by hemiplegia and diplegia. We found 60.8% of patients to have some degree of ocular disease. Visual field restrictions were found in 29.3% of patients, ranging from 30º to 100º, including restrictions superiorly and inferiorly. Contrast sensitivity mode was 1.25%. Saccadic and pursuit movement dysfunction was found in 13.7% and 15.6% of the cases. Eye-hand coordination was impaired in 16.6% of the patients. Conclusion: Patients with cerebral palsy often present with visual disturbances. The ophthalmologist should be aware of the most frequent visual dysfunctions and how to diagnose them. Also, appropriate management to enhance visual performance can have a significant impact on social interaction, autonomy, and quality of life in these patients.